GAMBARAN PERSEPSI REMAJA PUTRI TENTANG KEKERASAN DALAM PACARAN DI SMK NEGERI 01 NANGGULAN KULONPROGO - Yusuf, Nuuva; Riyan Ariestantia, Dwi; Diah Anggraini, Ryzky (Jurnal Kebidanan Mutiara Mahakam, 2019)
Dating violence is often found as community problem which is part of intimate partnerviolence but many adolescents do not understand and aware themselves as victims of violence. Theaim of the study was to describe the perceptions of young women about dating violence on femalestudents at dating violence of students of vocational school SMK Negeri 1Nanggulan KulonProgousing descriptive descriptive method with a cross sectional approach. Data analysis using Chi squarewith an error rate of 0.05. The results of this study on the perceptions of adolescents about violenceon female students of SMK Negeri 1 Nanggulan were 89 students (62.2%). Poor perception of 54female students (37.8%). Adolescents 'perceptions of violence both indicate that respondents have anunderstanding that violence is wrong and unnatural in a dating relationship and respondents'understanding is good about the form of violence